APPLICATION OF FREE COMPUTATIONAL PROGRAM IN EXPERIMENTAL DESIGN: A TUTORIAL - Verbi Pereira, Fabiola Manhas [UNESP]; Pereira-Filho, Edenir Rodrigues (Soc Brasileira Quimica, 2018)
This tutorial intends to show to the readers a step-by-step guide to perform a factorial design in their experiments. The examples used here cover most of doubts and questions related to teaching classes at graduation course. Free computational software was applied, as well as, codes were designed by the authors for the calculations. The complexity of each example is attached to the challenges and decisions that the experimentalist faces in its research. In addition, 24 videos were prepared to help the readers. The authors hope to foster the factorial design as an easy and helpful tool for chemists and general researchers in academia and industry.
Keywords: Octave; factorial design; analysis of variance; regression model; template surface